2012
DOI: 10.1016/j.sdentj.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Career characteristics and postgraduate education of female dentist graduates of the College of Dentistry at King Saud University, Saudi Arabia

Abstract: More than half (54%) the female dentists surveyed had pursued postgraduate education. This investigation highlighted the different specialties enrolled by female dentists. Orthodontic post graduate program displayed the highest percentage of interest. Understanding the unavoidable social family needs and the demand for higher education by female dentists provides ideas as more programs should be planned to accommodate the needs of Saudi female dentists. This type of study should be repeated due to the increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 7 publications
1
26
2
Order By: Relevance
“…Furthermore, the majority of female subjects preferred operative dentistry, followed by pediatric dentistry, which is in contrast to a previous Saudi study reporting that the majority of female dentists preferred orthodontics, followed by endodontics [11]. None of the postgraduate preferences of the male and female students concurred with the results of a cross-cultural study that reported that orthodontics was the first preference of Canadian and Japanese students [17].…”
Section: Discussioncontrasting
confidence: 70%
“…Furthermore, the majority of female subjects preferred operative dentistry, followed by pediatric dentistry, which is in contrast to a previous Saudi study reporting that the majority of female dentists preferred orthodontics, followed by endodontics [11]. None of the postgraduate preferences of the male and female students concurred with the results of a cross-cultural study that reported that orthodontics was the first preference of Canadian and Japanese students [17].…”
Section: Discussioncontrasting
confidence: 70%
“…Efforts of the Ministries can be supported by the academic institutions that are now widely established in the Arab peninsula. Colleges of dentistry are now established in almost all major cities in Saudi Arabia, attracting many students of both sexes, and this is reflected in the growing number of dental graduates 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the financial income, potential of growth, and the stressful working style are another factors to consider. He also found in another study that females are leaning more toward Orthodontics, Pediatrics, Endodontics, and Restorative dentistry with local PGDE to be more preferred due to the demanding social and family needs when compared to studying abroad [3,4,6]. On the other hand, male students preferred Orthodontics, Pediatrics, and Endodontic programs, as they might be more challenging and lucrative.…”
Section: Discussionmentioning
confidence: 97%
“…Advancing the quality of clinical skills as well as the research output will drive the medical and dental care forward by improving the service level, patient satisfaction, and reducing the complication rate [1,2]. Nowadays, the number of dental graduates in Saudi Arabia is exceeding 2500 from over 30 dental schools every year [3,4]. However, the general distribution to the different working domains has not been studied nor planned.…”
Section: Introductionmentioning
confidence: 99%